Modern Science vs. Vedic Science - Subhendu Das (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2019)
Light can be understood only if we know the darkness. Similarly, the truths can be fully comprehended only if you know the falsehoods also. Many western philosophers, like Mark Twain, said “Majority is always in the wrong.” To understand Vedic science one must therefore know: (a) The role played by the money power. The destiny of the entire earth is controlled by the money power. Without money none of us can survive. So, everything we do, do not do, and cannot do is motivated by our desire and security of money. (b) Yogic power, which is the highest level power, even above the money power, if you can acquire it. It controls the global destiny of the entire universe. (c) Modern science, which is the product of the global destiny, as well as the money power or the destiny of the earth.Once you understand destiny, you will of course not blame anybody, including global, earth, or individual destiny. We will show with examples that all results of modern science are based on  or derived from assumptions. Since assumptions cannot be valid for nature and engineering,  modern  science therefore cannot represent the nature, and be applicable to nature and engineering. For the same reason results of modern science can never be demonstrated. It must be realized that there is a heaven   and hell difference between modern science and modern engineering. Since engineering uses science, all of engineering is full of patches and kludges, and therefore engineering is very unreliable, and pollutes environment. On the other hand the Vedic science is entirely based on observations, just like what Galileo observed. Vedic science does not therefore has any assumptions, and it is a record of what you see as happening in nature. The Vedic science also has another very crucial difference – it observed two types of causes: (a) efficient cause and (b) material cause, behind every phenomenon. As a result Vedic science is valid for the entire universe and for all time, past, present, and future. We will illustrate all results of Vedic science with observations in nature. Such examples will be beyond comprehension of modern science.